ТИЛНИНГ ПАЙДО БЎЛИШ МУАММОСИГА ОИД ҚАРАШЛАР (Scientific journal of the Fergana State University, 2023)
The article elucidates various problems upon appearing of a language and views on their philosophical, psychological, sociological and philological relations.